Wocheinite - Bauxite from Bohinj - Razinger, Borut (Geologija, 1997)
Only few Slovenians except for geologists and experts for bauxite know the bauxite variety called wocheinite that was mined in Bohinj since 1868. This was the time when various new aluminium minerals were discovered (bauxite, kljakite) and usually named after the localities of their occurrence. Later it was discovered that aluminium ore bauxite was a mixture of distinct aluminium minerals: hydrargilite (gibbsite), boehmite and diaspore, and in addition several iron minerals that give the ore its colour. Therefore here these important aluminium minerals are described. Chemical and mineralogical determinations of several wocheinite samples collected at the vilage of Brod suggest the hydrargilite-boehmite type of bauxite, and with respect to iron the goethite-hematite variety. In the paper also the information on the bauxite mine and mining in Bohinj is summarized.